Psychological Profile of Taekwondo Athletes : Cross – Sectional Study - Angela Cornellia; Hadi; Dewangga Yudhistira (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Taekwondo is a martial arts sport that emphasizes the use of hands and feet. Important aspects include technique, tactics, physicality, strategy, and mentality, with a focus on psychology. Psychology in taekwondo includes motivation and anxiety management. Effective stress management is essential during athletes' preparation for competition. Athletes with high levels of motivation tend to employ more effective coping strategies and perceive stress more positively. Coaches and support teams play an important role in supporting athlete motivation, requiring a holistic approach to stress control and performance enchancement. Mental skill help athletes process psychological stress. This study used a descriptive research method with a cross sectional approach, conducted over one month. The subjects were 45 taekwondo athletes aged 20–25 years with at least five years of training experience and active at the provincial level. Results showed that most athletes demonstrated high levels of stress control, motivation, and mental skills, with 59% in the “agree” and 16% in the “strongly agree” category, indicating good psychological readiness though some variations remained. Overall, the study concludes that taekwondo athletes possess a positive psychological profile that supports performance, and the CPRD instrument is effective for evaluating and planning psychological interventions.